Impact Of Goods And Services Tax On Fmcg Sector (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose: The Purpose of this study is to examine the functional relationship between goods and services tax and purchasing power of fast moving consumer goods consumers. The other purposes of the study is to examine the impact of goods and services tax on this sector and subsequent implications for industry stakeholders.Methodology: The data required for this study is collected through both primary and secondary sources. This research is quantitative in nature and IBM SPSS25 version software is used for data processing and analysis.Findings: The study identifies a significant and positive relationship between goods and services tax and purchasing power of consumers. The opposite kind of relationship exist between various performance parameters of FMCG sector.Implications: The results of the study clearly has created a significant impact on the purchasing power of the consumers and the study suggests marginal cost pricing for FMCG products so that the burden of indirect tax is minimized.Originality: This study is unique because it brings together both industry and consumer perspectives of goods and services tax and its implication for industry stakeholders.